Social Portraits and Educational in Street Children Film - Jaka Farih Agustian (SANGKÃ©P: Jurnal Kajian Sosial Keagamaan, 2023)
The character education values in movies and contexts and social functions can be relevated and implemented in the schools and universities.Â Some of the educational values of the characters in the film include religious, honestly, and discipline, hard work, creativity, self-sufficiency, the spirit of nationality, and responsibility. How successful the film is in the learning of communication, they can be used in teaching materials. can be expressed and implemented in the daily life of students, like a religious attitude, hard work, creativity, and so on. Then you can use the media to dig creative ideas to write stories. Alangkah Lucunya Negeri Ini constructing the problems of the country of Indonesia, especially in the case of street children. In the film also teaches how street children also have to have a struggle to reach the point of success of a nation. The data in this study of the text from the transcription of dialogue from a film onto words shaped in the form of text and that god is adapted to this main research study. While the data here as a data acquisition will be analyzed. At this stage, look for and collect text conducted by researchers team. Data validation or validity of data in this study by means of collected data. The data collected, collected, and recorded in research activities were selected in right in developing the validity of the data